2015
DOI: 10.1152/ajpgi.00281.2014
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between hydrogen sulfide-induced sulfhydration and tyrosine nitration in the KATP channel complex

Abstract: Hydrogen sulfide (H₂S) is an endogenous gaseous mediator affecting many physiological and pathophysiological conditions. Enhanced expression of H2S and reactive nitrogen/oxygen species (RNS/ROS) during inflammation alters cellular excitability via modulation of ion channel function. Sulfhydration of cysteine residues and tyrosine nitration are the posttranslational modifications induced by H₂S and RNS, respectively. The objective of this study was to define the interaction between tyrosine nitration and cystei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…This might be the key mechanism for H 2 S to act as an endothelial derived relaxing factor. Kang et al also found that H 2 S increased S‐sulfhydration on sulphonylurea 2B (SUR2B) at Cys24 and Cys1455, another subunit of K ATP channels complex, to restore smooth muscle contraction (Kang et al, ). Liu et al found that H 2 S decreased the membrane potential, inhibited the fast inactivation component of the voltage‐dependent potassium channel current in gastric smooth muscle cells and promoted gastric motility, which was suppressed by KV4.3 knockdown.…”
Section: H2s Induced Protein S‐sulfhydrationmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be the key mechanism for H 2 S to act as an endothelial derived relaxing factor. Kang et al also found that H 2 S increased S‐sulfhydration on sulphonylurea 2B (SUR2B) at Cys24 and Cys1455, another subunit of K ATP channels complex, to restore smooth muscle contraction (Kang et al, ). Liu et al found that H 2 S decreased the membrane potential, inhibited the fast inactivation component of the voltage‐dependent potassium channel current in gastric smooth muscle cells and promoted gastric motility, which was suppressed by KV4.3 knockdown.…”
Section: H2s Induced Protein S‐sulfhydrationmentioning
confidence: 99%
“…That is S‐sulfhydration of SUB2B at C24S and C1455S inhibited the nitration of K ir 6.1. Moreover, NaHS also reduced the tyrosine nitration of Ca v 1.2b channels to improve Ca 2+ ‐induced contractions in mouse ileum (Kang et al, ). In accord with the previous study, NaHS reduced the activity of L‐Ca 2+ channels containing free sulfhydryl groups in cardiomyocytes (Zhang et al, ).…”
Section: Crosstalk With Protein S‐sulfhydration and Other Post‐translmentioning
confidence: 99%
“…In lymphatic vessels of TNBS-inflamed guinea pig ileum, NO stimulates the cGMP/ PKG pathway, upregulating mRNA level and activity of K ATP channels, which impairs lymphatic pumping (96). On the other hand, hydrogen sulfide (H 2 S) beneficial effects on colitis severity and mortality have been attributed to the activation of K ATP channels through S-sulfhydration of the SUR2B subunit (47,65,140). K ATP channels are present in the basolateral membrane of the rat colonocytes, but their exact composition is still unknown (109).…”
Section: Rbhi T Cells Into Rag2mentioning
confidence: 99%
“…Although biochemical regulation of the K ATP channel function is incompletely understood, particularly in the brain, a number of post-translational modifications have been reported. For example, SUR2 is affected directly by glycosylation, sulfhydration, and protein kinase A phosphorylation (Gade, et al, 2013,Gao, et al, 2014,Kang, et al, 2014,Light, 1996). The K ATP channel is also regulated via separate phosphorylation event(s) in the Kir6.x channels (Edwards, et al, 2009,Ko, et al, 2008,Sanada and Kitakaze, 2004,Sun, et al, 2008), again showing complex functional interdependence of these proteins.…”
Section: Abcc9/sur2 Function: Biochemistry and Physiologymentioning
confidence: 99%